Literature : - DiYanni, Robert (McGraw-Hill, 2002)
This anthology provides broad coverage for the three genres of literature--fiction, poetry, and drama--and exceptionally clear presentation of the elements of literature. The text has a clear and up-to-date chapter on critical theory that features helpful checklists